2017
DOI: 10.1101/129106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissecting telomere maintenance mechanisms in pediatric glioblastoma

Abstract: Pediatric glioblastoma (pedGBM) represent a highly malignant primary brain tumor with recurrent mutations in the chromatin remodeler ATRX and the histone variant H3.3 that is typically associated with a fatal outcome. ATRX acts as suppressor of the alternative lengthening of telomeres (ALT) pathway, which is frequently activated in pedGBM. However, telomere features of pedGBMs have not been studied in detail, and ALT-positive model cell lines are lacking. Here, we systematically characterized a panel of pedGBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…Each of the six tumors analyzed showed the same hypomethylated promoter status. The association between promoter hypomethylation and low expression has also been reported for human TERT in brain cancer (Deeg et al, 2017). This relation suggests that promoter hypomethylation is a general feature of negative regulation of tert expression, perhaps due to the location of the gene in a subtelomeric region (CHR5:1253147-1295069, GRCh38/hg38), both in human and in zebrafish (Figure 2C, inset).…”
Section: Telomerase Is Not Involved In Tmm In Zebrafish Brain Tumorssupporting
confidence: 65%
See 1 more Smart Citation
“…Each of the six tumors analyzed showed the same hypomethylated promoter status. The association between promoter hypomethylation and low expression has also been reported for human TERT in brain cancer (Deeg et al, 2017). This relation suggests that promoter hypomethylation is a general feature of negative regulation of tert expression, perhaps due to the location of the gene in a subtelomeric region (CHR5:1253147-1295069, GRCh38/hg38), both in human and in zebrafish (Figure 2C, inset).…”
Section: Telomerase Is Not Involved In Tmm In Zebrafish Brain Tumorssupporting
confidence: 65%
“…We found that zebrafish tumors rely on ALT as TMM, similarly to many pediatric GBMs. With the increasing number of reports documenting a prevalence of ALT in some pediatric cancers (Heaphy et al, 2011;Dorris et al, 2014;Deeg et al, 2017) the role of the embryonic origin of these tumors in the ability to activate telomerase or ALT during cancer progression is becoming evident.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the six tumours analyzed showed the same hypomethylated promoter status. The association between promoter hypomethylation and low expression has been reported also for human TERT in brain cancer 33 . This relation suggests that promoter hypomethylation is a general feature of negative regulation of tert expression, perhaps due to the location of the gene in a subtelomeric region (CHR5:1253147-1295069, GRCh38/hg38), both in human and in zebrafish (Figure 2c, inset).…”
Section: Telomerase Is Not Involved In Tmm In Zebrafish Brain Tumoursmentioning
confidence: 61%
“…These experiments confirmed an increase in TERRA levels in tumors as compared to control brains (Figure 4e), which is consistent with the RNA-FISH results. Finally, TERRA expression levels were quantified by performing quantitative reverse transcription PCR using total RNA obtained from control and brain tumours 33 and compared to TERRA levels in HeLa and U2OS cells. By these analyses, we found that TERRA levels in tumours were almost 3-fold higher than in control brains (Figure 4f, left panel).…”
Section: Co-fish 36 Experimentsmentioning
confidence: 99%
“…Furthermore, little evidence was found for ALT in these tumors, with only one sample being positive in a study comprising 60 tumor specimens [180]. In contrast, about half of all pediatric high grade gliomas (PHGGs) is positive for ALT, and a smaller subgroup of about 23% has activated telomerase, with TERT promoter mutations and chromothripsis being quite uncommon [104,180,199,243]. Adult high-grade gliomas show the reverse pattern [243].…”
Section: Brain Tumorsmentioning
confidence: 99%